Computational methods in elementary numerical analysis - Morris, J. Ll. ([S.l.] : Wiley, 1983)
This self-contained introductory text stresses a ``learn by doing' approach to numerical analysis with exercises to be done on a computer or micro-computer. Unlike ``software'' books, this text thoroughly explains methods used for solving problems with sufficient analysis to show why$1 (Band why not$1 (Bthey work. Discussions of theorem proofs are kept to a minims